Conhecendo a vulnerabilidade ao HIV/AIDS de dois grupos de idosos - Santos, Jiovana de Souza (2018)
Initial considerations: concomitant to increased life expectancy, there was growth in rates of infection by the aids virus in the elderly. The high incidence of infection in the age group of 60 years and reveals the need to investigate the factors that are related to this increase in order to obtain subsidies to aid in the control of the epidemic. Objective: highlight the knowledge produced in the scientific literature about the vulnerability to HIV/Aids of elderly people and analyze the relationship between the educational level and vulnerability to HIV/Aids of elderly people. Methodological pathway: an integrative review of the literature of the last ten years in order to meet the vulnerabilities to HIV/Aids. Later we performed field research a comparative study, exploratory, directed with 100 elderly registered in family health Units in the city of João Pessoa, Paraíba. Half of the elderly have higher educational level and half below grade level. The data were collected in the period from July to December 2017 through a questionnaire which includes demographic data and questions about vulnerability to HIV/Aids. The data were processed by the program SPSS 19 through descriptive statistics with nonparametric Chi-square test, Alpha Cronbach's alpha trust measurement and test of nonparametric Mann-Whitney. The research was approved by the Research Ethics Committee of the Health Sciences Center/CCS/UFPB as CAAE 67103917.6.0000.5188 CAA. Results: the study of integrative literature review the vulnerability to HIV/Aids of elderly were evidenced by: behaviors, practices, knowledge and social representations, identified by active sexual life, low adhesion of the use of condom related to confidence in the partner; the elderly do not fall in the HIV/Aids scenario, see as another disease; knowledge is incipient, vulnerability prevention, but not practice. Most elderly 54 (54%) are women between the ages of 60 to 70 years (80%); 55 (55%) are married. Of respondents, 50 (50%) feature complete higher education and the remaining 20 (20%), followed by 18 (18%) illiterate and 12 (12%) with high school; 80 (80%) are of the Catholic religion. As for participation in family income 51 (51%) contribute to supplementary form. The data reveal that the vulnerability to HIV/Aids of elderly with low level of schooling is two times higher than in older people with higher education. The average was 7.14 and standard deviation of the average 3.66 against 3.22 and 1.49 respectively and standard deviation value of 0.001 Mann-'. < There was no difference in the responses of vulnerability as a whole. Most of the items the vulnerability is greater for the group that does not have higher education. However, in some items the vulnerability is quite similar for both groups. The items presented higher vulnerability to both groups on items 1, 2, 3 and 14 when not compared by group. As for items of greater vulnerability for group, the items more attention were the items 3, 4, 5, 9, 12 and 13 to the Group of seniors who do not have higher education. The Chi-square test was applied to evaluate the difference in occurrence in the answers on items. In all these items there is a statistically significant difference of opinion for these levels of schooling. There was little change in the extent of Cronbach's Alpha showing the items contributed evenly to the vulnerability information proposed by the instrument and that the measure Alpha to all items of the instrument was 0.805 with 95% of interval confidence between the 0.744 0.856. Final considerations: the increased cases of HIV/Aids on the elderly population is a public health problem. Noted gaps that threaten control of the aids epidemic when it highlights the vulnerability to HIV/Aids of elderly population, especially those with low level of education, because it is a demographic factor that hinders the access to information. On the results exposed, it becomes important that public policy aimed at preventing HIV from inserting the elderly audience in their actions. Suggests the use of active and innovative technologies to achieve this target audience, considering the homogeneity of this population. And above all, training for professionals who work primarily in the basic attention regarding the approach to the elderly about the dimensions involving the sexuality of the elderly, deconstructing images and stereotypes about the sex life of the elderly population.